Teriparatide in the management of osteoporosis - Donald Bodenner (Dove Medical Press, 2008)
Donald Bodenner, Carolyn Redman, Ann RiggsDepartment of Geriatrics, University of Arkansas for Medical Sciences, Little Rock, AR, USAAbstract: Fracture of the hip is frequently a catastrophic event in the elderly, often resulting in death within a year and of the survivors, few regain pre-fracture quality of life. Although less appreciated, fractures of the spine result in significant morbidity and are also associated with increased mortality compared with individuals without a fracture. In recent years there has been an explosion in the development of new drugs for the treatment of osteoporosis. Recombinant human parathyroid hormone (1–34) (20 μg/day) is a recent addition to this armamentarium with a novel mechanism of action, which was approved by the US FDA for the treatment of postmenopausal osteoporosis and male osteoporosis secondary to hypogonadism in November 2002. It is the first osteoporosis treatment that leads to the formation of new bone with architecture similar to normal bone. Intense efforts have been made to understand the effect of teriparatide on antiresorptive therapy and vice versa. Although these relationships are not completely understood, the results of recent studies allow clinicians to begin to optimize therapeutic gains in bone mineral density and improve anti-fracture efficacy.Keywords: osteoporosis, teriparatide, fracture